Study of the cost variation analysis of anti-epileptic drugs available in different brands in Indian pharmaceutical market - Kumar, Hansraj; Kesari, Uma Shankar Prasad; Kumar, Rajiv (International Journal of Basic & Clinical Pharmacology, 2021)
Background: The aim of this study was to analyze the cost ratio and percentage cost variations in different brands of the commonly prescribed anti-epileptic drugs available in Indian pharmaceutical market. Methods: The maximum and minimum price of each brand of the drug given in Indian rupees (INR) was noted by using CIMS January to April 2020 edition and drug today April to June 2020 volume 1. The cost ratio and the percentage cost variation for individual drug brands was calculated. The cost of one bottle in case of 100 ml syrup and 10 tablets/capsules was calculated in case of oral drugs and the cost of one 1 vial or ampoule was noted in case of injectable drugs. At last the cost ratio and percentage cost variation of various brands was compared. Results: After calculation of cost ratio and percentage cost variation for each brand of anti-epileptic drug tablet clonazepam (2 mg) shows highest cost ratio and percentage cost variation as 10.41 and 941.66, carbamazepine (200 mg SR tablet) shows lowest cost ratio and percentage cost variation as 1.09 and 9.32. Conclusions: Epilepsy is the most common neurological disorder and epileptic drugs are to be prescribed for prolonged period. If a costly brand is prescribed, the patients have to pay more money unnecessarily for their treatment. There is a wide difference in the cost of different brands of anti-epileptic drugs available in India. The clinicians prescribing these drugs should be aware of these variations in cost to reduce the cost of drug therapy.